Soehngenia longivitae sp. nov., a Fermenting Bacterium Isolated from a Petroleum Reservoir in Azerbaijan, and Emended Description of the Genus Soehngenia - Tamara N. Nazina; Salimat K. Bidzhieva; Denis S. Grouzdev; Diyana S. Sokolova; Tatyana P. Tourova; Sofiya N. Parshina; Alexander N. Avtukh; Andrey B. Poltaraus; Azhdar K. Talybly (Microorganisms, 2020)
A methanogenic enrichment growing on a medium with methanol was obtained from a petroleum reservoir (Republic of Azerbaijan) and stored for 33 years without transfers to fresh medium. High-throughput sequencing of the V4 region of the 16S rRNA gene revealed members of the genera Desulfovibrio, Soehngenia, Thermovirga, Petrimonas, Methanosarcina, and Methanomethylovorans. A novel gram-positive, rod-shaped, anaerobic fermentative bacterium, strain 1933PT, was isolated from this enrichment and characterized. The strain grew at 13–55 °C (optimum 35 °C), with 0–3.0% (w/v) NaCl (optimum 0–2.0%) and in the pH range of 6.7–8.0 (optimum pH 7.0). The 16S rRNA gene sequence similarity, the average nucleotide identity (ANI) and in silico DNA–DNA hybridization (dDDH) values between strain 1933PT and the type strain of the most closely related species Soehngenia saccharolytica DSM 12858T were 98.5%, 70.5%, and 22.6%, respectively, and were below the threshold accepted for species demarcation. Genome-based phylogenomic analysis and physiological and biochemical characterization of the strain 1933PT (VKM B-3382T = KCTC 15984T) confirmed its affiliation to a novel species of the genus Soehngenia, for which the name Soehngenia longivitae sp. nov. is proposed. Genome analysis suggests that the new strain has potential in the degradation of proteinaceous components.